Structural Relationship of Teachers’ Interaction Styles Based on Social Adaptability, Psychological Hardiness, and Academic Achievement Motivation with Mental Health Mediation in Eighth Grade Female Students - Rahmati, Fatemeh; Safaei Rad, Iraj; KhorramAbadi, Yadullah (Iranian Journal of Educational Sociology, 2022)
Purpose: The interaction styles of teachers play a significant role in improving both academic and non-academic outcomes for students. Thus, this study aimed to determine the structural relationship of teachers' interaction styles based on social adaptability, psychological hardiness, and academic achievement motivation with mental health mediation in eighth grade female students. Methodology: This study was applied in its objective and cross-sectional in its execution, utilizing a correlational type. The population of this study comprised all eighth-grade female students in the city of Kangavar in the academic year 1401-1402, totaling 2417 students. Based on the Krejcie and Morgan table, 379 of them were selected as the sample through multi-stage cluster random sampling. Data collection tools included questionnaires on teachers' interaction styles, social adaptability, psychological hardiness, academic achievement motivation, and mental health, which were analyzed using the Structural Equation Modeling (SEM) method in Amos software. Findings: The findings of this study indicated that the variables of social adaptability, psychological hardiness, and academic achievement motivation had a direct and significant effect on mental health, and the variables of social adaptability, psychological hardiness, academic achievement motivation, and mental health had a direct and significant effect on teachers' interaction styles. Moreover, the variables of social adaptability, psychological hardiness, and academic achievement motivation had an indirect and significant effect on teachers' interaction styles through the mediation of mental health (P